Augmented Reality as an ontological tool to access televised audiovisual information: Value for the journalist and for the viewer - Caldera-Serrano, Jorge; León-Moreno, José-Antonio (Cuadernos de Documentación Multimedia, 2020)
A theoretical development is presented of the access to audiovisual content for both journalists and viewers through the Web. This access is possible through virtual platforms using an ontological tool that displays the content through Augmented Reality in such a way that the relationships between and accesses to different ontological levels are carried out using visual elements, determining their value prior to download. Ontological relationships are established between traditional elements indexed in the audiovisual departments of television channels: persons, topics, and places, as well as other elements deriving from them. A brief description is given of the ontologies and their relationship with what is audiovisual, as well as experiences on television with Augmented Reality. The originality of the paper lies in the absence of previously proposed or developed experiences by any of the mass media